PENGARUH PENYARADAN KAYU DENGAN TRAKTOR RANTAI KELABANG TERHADAP KERUSAKAN TEGAKAN TINGGAL - Maman Mansyur Idris; Yahya Fakuara; Gunarwan Suratmo; Rahardjo S Suparto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The study of the effect of log skidding on the damage of residual stand was carried out in one logging company in West Kalimantan in 1986. The meaning of residual stand in the study are trees with diameter 20 cm and up. The result of the study shows that the average damage of residual stand is 18% per hectare, not included the damage caused by felling i.e. 15% per hectare. According lo Indonesian Selective Cutting System, the residual stand is good enough to fulfill the sustained yield condition, that is keep at least 25 core trees to be left per hectare. The role of skidded trees number and stand density was significant effect on the residual stand damage.